Evaluasi Kinerja DAS Warjori Berdasarkan Kejadian Banjir dan Longsor di Kampung Jim Kabupaten Pegunungan Arfak - Andi Munawir; Rudi A. Maturbongs Eboni; Bernadetta M. G. Sadsoeitoeboen, Eboni (Program Studi Kehutanan Universitas Muslim Maros, 2026)
The Warjori Watershed is one of the strategic watersheds in West Papua that functions as a water regulation system, erosion controller, and ecological support for the surrounding communities. On May 16, 2025, flash floods and landslides occurred in Jim Village, Catubouw District, Arfak Mountains Regency, which is located within the Warjori Watershed area. This study aimed to evaluate the performance of the Warjori Watershed based on flood and landslide event parameters through the analysis of rainfall, land cover, critical land conditions, soil types, and human activities. The research employed a quantitative descriptive approach using spatial analysis and desk analysis based on the 2025 monitoring and evaluation data from BPDAS Remu Ransiki. The results showed that the Warjori Watershed has a high level of vulnerability to hydrometeorological disasters. Extreme rainfall reaching 123.44 mm/day prior to the disaster caused soil saturation and increased surface runoff. Land cover within the watershed is still dominated by primary dryland forest covering 65.95% of the area; however, critical land conditions reached 95.28%, categorized as moderately critical to very critical. In addition to natural factors, illegal gold mining activities have also intensified the risk of landslides and flooding. This evaluation indicates that the hydrological function of the Warjori Watershed has declined, thereby requiring integrated watershed rehabilitation, control of illegal activities, and strengthened disaster mitigation efforts to support sustainable watershed management in West Papua.